Day 4 Thu, June 06, 2019 2019
DOI: 10.2118/195474-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery of Heavy Oil by a Nano-Catalytic In-Situ Upgrading Process

Abstract: Simultaneous in-reservoir upgrading and recovery of heavy oil are experimentally studied by using a continuous setup filled with carbonate cores. Upgrading reaction products as well as the recovered oil are analyzed in order to investigate the recovery mechanisms associated with this process. In-situ upgrading technology (ISUT) is based on injection of high molecular weight (low quality) cut of oil, e.g., vacuum residue (VR), together with ultradispersed nano-catalyst and hydrogen. By injecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This behavior could be observed in all of the cases evaluated where there was a reduction in viscosity of up to 13% additional regarding the tests without its presence, as shown in Figure . This test allowed us to confirm the hypotheses proposed by several authors, ,, which concluded that the presence of clay minerals can lead to an additional decrease in this physical property, as was shown for the 70% sand scenarios where the higher clay content was added. The results show that the effect of metal ions from iron naphthenate on the viscosity of the enhanced base crude is also beneficial.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This behavior could be observed in all of the cases evaluated where there was a reduction in viscosity of up to 13% additional regarding the tests without its presence, as shown in Figure . This test allowed us to confirm the hypotheses proposed by several authors, ,, which concluded that the presence of clay minerals can lead to an additional decrease in this physical property, as was shown for the 70% sand scenarios where the higher clay content was added. The results show that the effect of metal ions from iron naphthenate on the viscosity of the enhanced base crude is also beneficial.…”
Section: Resultssupporting
confidence: 81%
“…High proportions of thermal distillation of crude light fractions were evidenced in higher proportion in siltstones because of their abundance in kaolinite with a higher surface area. In addition, Elahi et al 40 experimentally studied the use of a nanocatalyst in a continuous steam injection in a carbonate reservoir, obtaining an 8°API increase and more than 99% decrease in viscosity. Zhang et al 41 set out their experimental tests to quantify the effect of rock fragments into the aquathermolysis reaction on gas production.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersed metallic catalytic particles of high static energy density has been determined to get irreversibly adsorbed over the polar reservoir rocks. 21,22,29,35,36 In the present study, ICP spectroscopy confirmed practical total adsorption of dispersed metal particles by the rock, determined as the difference of the entering stream rich in metal particles minus metal contents for oils exiting the experimental reservoir units. Metals were analyzed first by sample mineralization (HNO 3 Sigma-Aldrich 438073, 70%; 10 mL/0.5 g sample) using microwave-assisted digestion in a commercial unit model MARS 6 from CEM Corporation (Matthews, NC, USA) and afterward followed by ICP-atomic emission spectroscopy with an IRIS Intrepid II XDL spectrometer from Thermo-Instruments Canada, Inc., Ontario, Canada.…”
Section: Continuous Operating Unitsupporting
confidence: 72%
“…The ISUT process was initially designed for sand reservoirs but has been explored for use in fractured carbonate reservoirs. It leverages the reservoir as a reactor, anchoring metallic ultradispersed catalysts onto minerals for in situ upgrading. Vacuum residue (VR) serves as the carrier fluid, containing heat, catalysts (100–700 ppm metals), and hydrogen (50–300 std cm 3 per std cm 3 of VR) .…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of steam, both under H 2 -only or N 2 -only environments, the yield of CO 2 is marginal, which is in agreement with previous similar studies in our group for similar sets of experiments. 37,38 In addition, for the case of H 2 : N 2 of 1 : 1, there is no significant CO 2 production, whereas if any of these two gases is replaced with steam, i.e. the two cases of H 2 : H 2 O or N 2 : H 2 O of 1 : 1, the CO 2 yield is markedly higher.…”
Section: Resultsmentioning
confidence: 99%